ANALISIS PENGARUH STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PERUSAHAAN - Ika Puspita Kristianti (Universitas Sarjanawiyata Tamansiswa, 2018)
The objective of this study is to empirically identify the impacts of capital structure chosen by company on firm’s financial perfomances. This research examine the effects of variable Debt to Asset Ratio (DR) and Debt to Equity Ratio (DER), partially and simultaneously to Return on Assets and Return on Equity. This research analyze secondary data using cross sectional method. The research specifically choose multi-finance companies that listed in Indonesia Stock Exchange as research population, with consideration of the characteristics and unique business risk level. The result of hypotheses tests proves that capital structure has a significant effect to firm’s financial performance. The added of debt proportion will affect added interest expense, which will lower the asset’s effectivity to earn income. On contrary, higher debt also gives positive impact for income. Higher debt means more resources that could be used by firm in maximizing business opportunity. This result is relevant with firm’s business process that provide financial services to its customers. The more funds that firms could provide for its customers, then there will be higher opportunities for the firm to get higher interest income. The objective of this study is to empirically identify the impacts of capital structure chosen by company on firm’s financial perfomances. This research examine the effects of variable Debt to Asset Ratio (DR) and Debt to Equity Ratio (DER), partially and simultaneously to Return on Assets and Return on Equity. This research analyze secondary data using cross sectional method. The research specifically choose multi-finance companies that listed in Indonesia Stock Exchange as research population, with consideration of the characteristics and unique business risk level. The result of hypotheses tests proves that capital structure has a significant effect to firm’s financial performance. The added of debt proportion will affect added interest expense, which will lower the asset’s effectivity to earn income. On contrary, higher debt also gives positive impact for income. Higher debt means more resources that could be used by firm in maximizing business opportunity. This result is relevant with firm’s business process that provide financial services to its customers. The more funds that firms could provide for its customers, then there will be higher opportunities for the firm to get higher interest income. Key words: capital structure, financial performance, profitability